CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon
MyQuestionIcon
Question

Which of the following differential equations has as the general solution? A. B. C. D.

Open in App
Solution

The equation is given as,

y= c 1 e x + c 2 e x

Differentiate both sides of above equation with respect to x,

d dx ( y )= d dx ( c 1 e x + c 2 e x ) y = c 1 e x c 2 e x

Again differentiate above equation with respect to x,

d dx ( y )= d dx ( c 1 e x c 2 e x ) y = c 1 e x + c 2 e x d 2 y d x 2 =y d 2 y d x 2 y=0

Therefore, option B is correct.


flag
Suggest Corrections
thumbs-up
0
BNAT
mid-banner-image